Building global democracy? : civil society and accountable global governance - Scholte, Jan Aart. (Cambridge, UK : Cambridge University Press, 2011)
'The scale, effectiveness and legitimacy of global governance lag far behind the world's needs. This path-breaking book examines how far civil society involvement provides an answer to these problems. Does civil society make global governance more democratic? Have citizen action groups raised the accountability of global bodies that deal with challenges such as climate change, financial crises, conflict, disease and inequality? What circumstances have promoted (or blocked) civil society efforts to make global governance institutions more democratically accountable? What could improve these outcomes in the future? The authors base their argument on studies of thirteen global institutions, including the UN, G8, WTO, ICANN and IMF. Specialists from around the world critically assess what has and has not worked in efforts to make global bodies answer to publics as well as states. Combining intellectual depth and political relevance, Building Global Democracy? will appeal to students, researchers, activists and policymakers'--
Introduction / Jan Aart Scholte -- Global governance, accountability and civil society / Jan Aart Scholte -- Civil society and accountability of the United Nations / Kerstin Martens -- The World Bank and democratic accountability: the role of civil society / Alnoor Ebrahim and Steven Herz -- Civil society and IMF accountability / Jan Aart Scholte -- Civil society and the WTO: contesting accountability / Marc Williams -- Civil society and accountability in the Commonwealth / Timothy M. Shaw and Pamela K. Mbabazi -- The organisation of the Islamic conference, accountability and civil society / Saied Reza Ameli -- Civil society and patterns of accountability in the OECD / Morten Ougaard -- Civil society and G8 accountability / Peter I. Hajnal -- Structuring accountability: civil society and the Asia-Europe meeting / Julie Gilson -- Civil society and accountability in global governance of climate change / Peter Newell -- Civil society and accountability promotion in the global fund / Carolyn Long and Nata Duvvury -- Accountability in private global governance: ICANN and civil society / Mawaki Chango -- Civil society and the World Fair Trade Organisation: developing responsive accountability / Heidi Ullrich -- Conclusion / Jan Aart Scholte.
Includes bibliographical references (p. 343-380) and index.
Keywords: Democratization; Civil society; International organization